Mind-Body Wellness Program Development: Integrating Zumba Exercise and Mindfulness to Enhance Fat Metabolism and Mental Health - Surya Adi Saputra; Anton Komaini (Joska: Jurnal Isori Kampar, 2025)
Objectives: This study aimed to develop and evaluate a comprehensive mind-body wellness program that integrates Zumba exercise and mindfulness training to optimize fat metabolism and enhance mental health outcomes in sedentary adults. Methods: A quasi-experimental design was employed with 60 adult participants (aged 20-40) randomly assigned to an intervention group (n = 30) and a control group (n = 30). The intervention group underwent a 12-week program combining 3 sessions of Zumba (60 min each) and 2 mindfulness sessions (30 min each) per week. Comprehensive measurements included body mass index (BMI), body fat percentage, waist-to-hip ratio, fasting lipid profile, cortisol levels, Beck Depression Inventory-II (BDI-II), Perceived Stress Scale (PSS), Five Facet Mindfulness Questionnaire (FFMQ), and Physical Activity Enjoyment Scale (PACES). Data were analyzed using paired t-tests, independent t-tests, repeated measures ANOVA, and effect size calculations. Results: Participants in the intervention group showed significant reductions in BMI (-2.1 ± 0.4, p < 0.01), body fat percentage (-4.8%, p < 0.01), waist-to-hip ratio (-0.08 ± 0.02, p < 0.01), and stress levels (-6.2 ± 1.8, p < 0.01) compared to controls. Significant improvements were also observed in positive affect, mindfulness scores, exercise enjoyment, and cortisol regulation. Effect sizes were large for most outcome measures (Cohen's d > 0.8). Conclusion: The integration of Zumba exercise and mindfulness training in a structured wellness program effectively improved both metabolic and psychological health markers with sustained effects. These findings highlight the potential of hybrid physical-psychological interventions in holistic health promotion and provide evidence for community-based wellness programs